The adsorption-swelling and permeability characteristics of natural and reconstituted anthracite coals. (15th December 2017) - Niu, Qinghe; Cao, Liwen; Sang, Shuxun; Zhou, Xiaozhi; Wang, Zhenzhi; Wu, Zhiyong
Abstract: To fundamentally study the adsorption capacity, swelling effect and permeability characteristic of coal seams with and without tectonic damage, the natural coal and reconstituted coal manufactured via simulating in situ geological conditions were investigated. The results show that the reconstituted coal possesses higher adsorption equilibrium time and maximum adsorption capacity comparing to the natural coal. The multitudinous intergranular seepage paths and large specific surface area of it supply adequate opportunities and sites for adsorption of injected gas. The anisotropy swelling was observed in the natural coal, which is manifested as that the axial swelling strain surpasses the radial swelling strain. Contrarily, the swelling strain of reconstituted coal is approximated to homogeneous and isotropic variety. The natural coal possesses swelling hysteresis phenomenon in the low adsorption stage, this is because of the deformation sequence from internal swelling to volume swelling conducted in it. The permeability of natural coal and reconstituted coal decreases remarkably after being saturated CO2 and N2 . Especially, the permeability sensitivity of reconstituted coal is higher than natural coal and has enormous decreasing amplitude after injected high-pressure CO2, which reveals us that weak coal seams may be the unstable areas for CO2 -ECBM or CGS in deep coal seams. Highlights: The adsorption capacity of reconstituted coal and natural coal were compared. The different swelling models of reconstituted coal and natural coal were proposed. Reconstituted coal possesses larger permeability decreasing amplitude than natural coal. Weak coal seams may be the unstable areas for CO2-ECBM or CGS in coal seams.